Operative Management of Sciatic Nerve Palsy due to Impingement on the Metal Cage after Total Hip Revision: Case Report - Alessandro Bistolfi; Giuseppe Massazza; Davide Deledda; Elisa Lioce; Maurizio Crova (Case Reports in Medicine)
This paper discusses a sciatic nerve palsy developed after a right total hip revision with a Burch-Schneider metal cage. A sciatalgic nerve pain appeared after surgery, while the palsy developed in about fifteen days. An electromyography showed the delay of the nerve impulse gluteal level. During the surgical exploration of the hip, a compression of the nerve on the metal cage was observed. The nerve was isolated, released from the fibrotic tissue and from the impingement, and was protected with a muscular flap. The recover from the pain was immediate, while the palsy recovered one month later.